2011
DOI: 10.1088/0022-3727/44/34/345202
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field approaches in dc thermal plasma modelling

Abstract: The self-induced magnetic field has an important role in thermal plasma configurations generated by electric arcs as it generates velocity through Lorentz forces. In the models a good representation of the magnetic field is thus necessary. Several approaches exist to calculate the self-induced magnetic field such as the Maxwell–Ampere formulation, the vector potential approach combined with different kinds of boundary conditions or the Biot & Savart (B&S) formulation. The calculation of the self-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…The basis of the model is presented below. Additional details on the equations set and boundary conditions can be found in [1], [2], and [15].…”
Section: Model Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis of the model is presented below. Additional details on the equations set and boundary conditions can be found in [1], [2], and [15].…”
Section: Model Presentationmentioning
confidence: 99%
“…In this paper, the model already reported in [2] and [15] is used and completed. As numerous parameters can influence the changes in pressure and for ease of comparison with the experimental results, most parameters such as pin motion, current variation, and valve position (open/close) between the heating volume and the compression volume were determined by experimental measurements.…”
mentioning
confidence: 99%
“…As explained in Introduction, recent works examined the effect of the boundary conditions for the magnetic vector potential in the model of DC free-burning and constricted transferred arcs (Ref 14,37). They concluded that null flux of magnetic vector potential, at the boundaries inside the plasma torch and a null value at the outlet boundary (PVNF condition), can yield wrong predictions of the magnetic field when the null flux condition is applied on boundaries close to the arc core.…”
Section: Effect Of the Magnetic Vector Potential Boundary Condition Omentioning
confidence: 99%
“…This enables to obtain the radiative flux and its divergence. Additional details on the equations set and boundary conditions can be found in previous papers [5][6][7]. With copper vapours, specific source terms for ablation model have to be taken into account.…”
Section: Equationsmentioning
confidence: 99%